The Effect of Induced Optimism on Situational Pain Catastrophizing - Basten-Günther, Johanna; Peters, Madelon L.; Lautenbacher, Stefan (Frontiers in Psychology, 2022)
Background: There is broad evidence that optimism is associated with less pain, while pain catastrophizing leads to increased pain. The aim of this study was to examine whether experimentally induced optimism can reduce situational pain catastrophizing and whether this relation is moderated by dispositional optimism and/or dispositional pain catastrophizing. Methods: Situational pain catastrophizing during two thermal stimulations was measured in forty healthy participants with the Situational Catastrophizing Questionnaire. Between the two stimulations, the Best Possible Self imagery and writing task was performed to induce situational optimism in the experimental group while the control group wrote about their typical day. Questionnaires were administered to assess dispositional optimism (Life Orientation Test Revised) and dispositional pain catastrophizing (Pain Catastrophizing Scale). Results: There was a significant interaction between the optimism induction and trait pain catastrophizing: the association of trait pain catastrophizing with state pain catastrophizing was weakened after the optimism induction. No overall effect of induced optimism on situational pain catastrophizing and no significant moderating influence of trait optimism were found. Conclusions: The state optimism induction counteracted the manifestation of dispositional pain catastrophizing as situational pain catastrophizing. This implies that high trait pain catastrophizers benefitted more from the optimism induction, which is in line with resilience models stressing the buffering role of optimism. Keywords: pain; pain catastrophizing; optimism; resilience; positive psychology